No sex difference in digit ratios (2D:4D) in the traditional Yali of Papua and its meaning for the previous hypotheses on the inter‐populational variability in 2D:4D. Issue 2 (14th November 2017) - Marczak, Michalina; Misiak, Michał; Sorokowska, Agnieszka; Sorokowski, Piotr
Abstract: Objectives: The ratio between the 2nd and 4th digit (2D:4D) is considered to be a sexually dimorphic trait in humans, with males having on average lower 2D:4D values than females. However, significant inter‐ and intra‐sexual differences in digit ratios across populations have been reported. In order to further explore factors influencing the variability of 2D:4D, we performed a study among the Yali, a traditional population from Papua. Methods: We measured digit ratios of 79 adults (47 males) from the traditional Yali society, a polygamous group who inhabit a harsh high‐mountain environment almost directly on the equator. Results: Statistical analysis of the data show no significant inter‐sexual difference in digit ratios in our sample. Conclusions: We discuss the results in light of various factors that putatively shape the differences in digit ratios. We conclude that the results of our study contribute to the existing evidence suggesting that digit ratio might not be universally sexually dimorphic in humans.